Current State of Tolerance: The Holy Grail - Rathore R; Gunawansa N; Ajay Sharma; Ahmed Halawa (Archives of Clinical Nephrology - Peertechz Publications, 2017)
Research in Tolerance and Chimerism by Transplant immunologists for over half a century is akin to the pursuit of the Holy Grail. Animal experiments for inducing tolerance may not have been successful initially but in that process, our knowledge of the fascinating immune system has been greatly enriched. Understanding of innate and adaptive immune systems has paved the way for development of potent immunosuppression. However, achieving clinical or operational tolerance long term in renal transplant recipients in the absence of immunosuppression is the ultimate goal for clinicians. Reduction in immunosuppression will lower morbidity and mortality associated with heavy burden of immunosuppression. This review article will be of particular interest to clinicians involved in delivering care to renal transplant recipients. We have elucidated mechanisms of self-tolerance through central and peripheral tolerance, evolution of tolerogenic strategies,difference between macro and micro-chimerism, overview of successful protocols for inducing tolerance and recent work in the development of expanding regulatory cell lines. It is most encouraging to note progress using cellular therapies as reported by Immune Tolerance Network and by Transplant Research & Immunology group at Oxford. We may not be far from achieving clinical tolerance albeit with minimal if not completely immunosuppression free regimens in the longer term.